Language and online identities: the undercover policing of internet sexual crime - Grant, Tim (Cambridge University Press, 2020)
"This book provides an account of our theoretical approach to identity and its relationship with linguistic performance, particularly within the context of online criminal interactions and communities. We report on findings from a project investigating the assumption of identities online, drawing on Instant Messaging (IM) data from a variety of contexts, both 'real life' and experimental, in order to expound the implications of our approach for the training and professional practice of online undercover investigators"--